TARI BADEO SEBAGAI ASET WISATA BUDAYA MELAYU OKURA - Oktasari, Andi Dwi; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Badeo Kayangan dance is a cultural asset possessed by Okura Malay as a tourist attraction of culture in Okura village. This research aims to describe: (1) The grain attractions Badeo Dance as a cultural tourism asset in Okura village; (2) Function of Badeo dance as a tourist attraction in Okura village; (3) Packaging art of Badeo dance as a tourism asset Malay culture in Okura village. This research uses the qualitative method with an etnographic approach, the subject is Badeo dancer, the Okura indigenous stake holders and the loal community. Data collection techniques that do by deep interview, document study, participant observation and documentation. The data analysis used in this study selecting the research, collecting the data research, make a note of the research analysis and writing of research results. The results of this research in the show, Badeo Kayangan has the unique elements and distintive with its myth, the movement, the music, the players, the crokery and time of the show. Based the function, Badeo Kayangan dance be used as a traditional healing rituals and performing arts facilities. The conclusions of this study is the Badeo Kayangan dance as a potential cultural attractions, the dance has a potential to be developed as a tourism asset Malay culture in Okura vilage by utilizing the potential possessed attractions, formed a cultural tourism package performing arts creative and innovative, increase Badeo dance function of performing arts and entertainment, as well as make promotion efforts.Keywords : Badeo dance, asset, tourism culture, Malay